1980
DOI: 10.1021/je60087a026
|View full text |Cite
|
Sign up to set email alerts
|

Uranium and plutonium equilibriums in aqueous solutions to 200.degree.C

Abstract: Standard molal Gibbs energy of formation and entropy data for aqueous uranium and plutonium ions in all oxidation states and their complexes with OH™, Cl™, F™, C032™, P043™, and SO,2' are critically reviewed. Selected values are used In a modified Criss-Cobble entropy extrapolation to derive self-consistent analytical expressions for the temperature dependence of the standard molal Gibbs energies of formation of 74 aqueous species and, hence, the Gibbs energy changes and equilibrium constants of their complexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(68 citation statements)
references
References 27 publications
5
62
1
Order By: Relevance
“…Site studies indicate that coprecipitation of trace metals in secondary minerals controls the concentrations of these dissolved constituents (Linklater et al 1994). Lemire and Tremaine (1980) Pu(.HP04), Lemire and Tremaine (1980) P-%o3 Lemire and Tremaine (1980) PuO,(OH) (a) Lemire andTremaine (1980) PuF3 Lemire andTremaine (1980) PuO,(OH), Lemire and Tremaine (1 980) Pu(OH)4 Lemire and Tremaine (1980) . Pu0,HP04 Lemire and Tremaine (1 980) PUo2 Lemire and Tremaine (1980) where a is the capacity factor or ratio of the moles per unit volume of water-saturated solid, C,, to the moles per unit volume of liquid, C,.…”
Section: C432 Maqarin Area In Northern Jordanmentioning
confidence: 99%
See 1 more Smart Citation
“…Site studies indicate that coprecipitation of trace metals in secondary minerals controls the concentrations of these dissolved constituents (Linklater et al 1994). Lemire and Tremaine (1980) Pu(.HP04), Lemire and Tremaine (1980) P-%o3 Lemire and Tremaine (1980) PuO,(OH) (a) Lemire andTremaine (1980) PuF3 Lemire andTremaine (1980) PuO,(OH), Lemire and Tremaine (1 980) Pu(OH)4 Lemire and Tremaine (1980) . Pu0,HP04 Lemire and Tremaine (1 980) PUo2 Lemire and Tremaine (1980) where a is the capacity factor or ratio of the moles per unit volume of water-saturated solid, C,, to the moles per unit volume of liquid, C,.…”
Section: C432 Maqarin Area In Northern Jordanmentioning
confidence: 99%
“…Lemire and Tremaine (1980) Pu(.HP04), Lemire and Tremaine (1980) P-%o3 Lemire and Tremaine (1980) PuO,(OH) (a) Lemire andTremaine (1980) PuF3 Lemire andTremaine (1980) PuO,(OH), Lemire and Tremaine (1 980) Pu(OH)4 Lemire and Tremaine (1980) . Pu0,HP04 Lemire and Tremaine (1 980) PUo2 Lemire and Tremaine (1980) where a is the capacity factor or ratio of the moles per unit volume of water-saturated solid, C,, to the moles per unit volume of liquid, C,. The capacity factor is related to the K, by the equation where p is the dry bulk density of the porous media and K, is the amount of contaminant adsorbed per unit mass of porous = solid divided by the amount of contaminant per unit volume of liquid.…”
Section: C432 Maqarin Area In Northern Jordanmentioning
confidence: 99%
“…Several databases of thermodynamic properties of the actinides have been developed over the last three decades. Of historical importance are the compilations and reviews of Lemire and Tremaine (1980), Phillips et al (1988), andFuger et al (1990). The most recent comprehensive and consistent databases have been based on compilations produced by the Nuclear Energy Agency (NEA) for plutonium and neptunium (Lemire et al, 2001), americium , uranium (Grenthe et al, 1992) and technetium (Rard et al, 1999).…”
Section: Aqueous Speciation and Solubilitymentioning
confidence: 99%
“…Literature review identified only one source of higher temperature complex stability data for plutonium species (Lemire and Tremaine 1980). The data used in this report was derived from their work using theoretical calculations instead of actual measurements.…”
Section: Temperature Effectsmentioning
confidence: 99%
“…Sparse empirical data is found on the tank environment and only theoretical estimates are found of the thermodynamic data needed to calculate the effects of temperature, using known chemical constructs that rely on enthalpy and heat-capacity measurements. Using the estimation technique presented by Lemire and Tremaine (1980), the solubility for amorphous Pu(IV) oxidehydroxide would not be significantly affected by temperatures up to 100°C. Required thermodynamic data for even the simple system, Pu-OH-H,O, is not precisely known and is essentially nonexistent for complex systems, such as Pu-OH-C0,-H,O.…”
Section: Effects Of Other Parameters On Plutonium Solubilitymentioning
confidence: 99%